Analisis Manajemen Produksi Pertanian Hidroponik Berbasis IoT (Internet of Things) di Wisata Edukasi Arjuna Farm Kecamatan Tamansari Kota Tasikmalaya - Andena Nur Hikmatunnisa; Wilva Ramadayanti; Rina Nuryati (Mikroba : Jurnal Ilmu Tanaman, Sains Dan Teknologi Pertanian, 2024)
The tourism sector in Indonesia is growing rapidly thanks to the abundant natural, social, cultural and regional potential. One educational tourist attraction that is currently developing is Arjuna Farm in Tasikmalaya City, which offers the concept of integrating the agricultural and fisheries sectors with the application of IoT (Internet of Things) technology. This research aims to analyze the application of IoT technology to support hydroponic production management at Arjuna Farm, especially in increasing the effectiveness, efficiency and quality of agricultural products. The research used a case study approach with a qualitative descriptive method, involving direct observation, in-depth interviews with the main managers (Mr. Andi and Mrs. Selvi), as well as analysis of secondary data from various literary sources. The research location was chosen by purposive sampling, located at Jalan Situ Cibereum, Tamanjaya, Tamansari, Tasikmalaya City, during November 2024. The research results show that POAC (Planning, Organizing, Actuating and Controlling) based management is implemented well, supported by IoT systems such as automatic watering, drip irrigation. This technology enables efficient and real-time production management, thereby maintaining the quality and sustainability of harvests, as well as increasing the attractiveness of Arjuna Farm as an educational tourist attraction based on modern technology.